The Effect of Discovery Learning Model on the Indonesian Language Learning Outcomes at Grade IV Students of State Elementary School 124394 Pematangsiantar - Sadarwati Laia; Yanti Arasi Sidabutar; Eva Saryanti Panggabean (International Journal of Technology and Education Research, 2026)
This study aims to determine the effect of the Discovery Learning model on the Indonesian language learning outcomes of fourth-grade students at the UPTD of Public Elementary School 124394 Pematangsiantar in the 2025/2026 academic year. The study used a quantitative approach with a pretest–posttest control group design. The study subjects were 54 students, consisting of 27 students in grade IV A (experimental) and 27 students in grade IV B (control). The research instrument consisted of 10 essay questions (pretest) and 10 essay questions (posttest). These questions were tested for Aiken V, reliability, N-gain, normality, homogeneity, and hypothesis testing (t-test). The results showed a significant increase in the average pretest score of the experimental class, which was 32.41 and the control class, which was 54.63. After the treatment, the average posttest score of the experimental class increased to 91.48, while the control class's score increased to 76.41. The average N-Gain for the experimental class was 87.6404% (high category) and for the control class, 47.9874% (moderate category). The data were normally distributed and homogeneous (Sig. 0.674 > 0.05). An independent samples t-test on N-Gain showed a significance value of 0.000 (<0.05), thus concluding that the Discovery Learning model has a positive and significant effect on improving fourth-grade students' Indonesian language learning outcomes.